Methodology and Model of Technologistics Index - Çemberci, Murat; Civelek, Mustafa Emre; Uca, Nagehan; Artar, Okşan; Onursal, Serab (Journal of History Culture and Art Research, 2018)
In today’s competitive landscape, it is necessary for firms and countries to maintain a competitive edge so as to gain a new consciousness by bringing together technological knowledge and logistics mind. The name of this consciousness is Technologistics. Technologistics is a consciousness that provides a sustainable competitive advantage and advanced company performance to the firms that adds technological base and logistics mind to its management and operation processes. In this paper, it is aimed to develop an index to rank countries in terms of Technologistics performance. Therefore NRI, GII, LPI have been used and these indices have been linked to GDP according to the methodology of the new index. As a result of this paper, TLI was proposed as the most prominent indicator of competitive advantage.